The Effect Of Controlling Hyperglycemia On The Morbidity And Mortality Of Intensive Care Unit (ICU) Patients - Hiyam Al-Haqeesh; Abla Al-Bsoul; Hussein Shalan; Aysha Abedalhameed Al-khalaylah; Nares Musa Ahmad Hakouz; Jaafar Abu Abeeleh; Ahed J Alkhatib; Mahmoud A Abu Abeeleh (European Scientific Journal, ESJ, 2016)
Introduction: Hyperglycemia and insulin resistance are common in critically ill patients, even if they have not previously had diabetes, and the risk of mortality or significant morbidity is high among those who are treated in the intensive care unit (ICU) for more than 5 days. Objective: To assess the effect of glucose management protocol on mortality and morbidity in a heterogeneous population of critically ill adult patients. Design: A randomized controlled trial. Setting: A 24-bed medical-surgical intensive care unit (ICU) for adult patients at King Hussein Medical Center, the Royal Medical Services. Methods: A total of 50 patients who were considered to need intensive care for at least three days, were randomly assigned into two groups. The intervention group subjects were to undergo a glucose control protocol with insulin infusion titrated to maintain blood glucose level in a target range of 120-160 mg/dL; except septic patients, in whom the target was higher, 160- 180 mg/dL. Patients in the second group (control group) were treated by a conventional approach with reduction of blood glucose level only if the level was markedly elevated (>200 mg/dL) to maintain blood glucose level in a target range of 180-200 mg/dL. Results: After adjustment for baseline characteristics the 2 groups of patients were well matched, for age, sex, prevalence of diabetes mellitus, HbA1c value and distribution of diagnoses; the only significant difference was in the percentage of cardiovascular dysfunction, which was higher in the intervention group (p=0.047). After institution of the protocol, the mean blood glucose levels differed significantly between the two treatment groups during the study period (143.70±12.78 mg/dL in the intervention group versus 175.56±14.07 mg/dL in the control group (p<0.001). And patients in the intervention group received a larger mean insulin dose 28.32 ±16.38 units per day, vs. 14.60±12.26 in the control group (p=0.001). The difference in mortality between the two treatment groups was not significant at 28 days (p=0.370) and at 60 days (p=0.555). No significant increase in hypoglycemia episodes was reported in our blood glucose level target. Conclusion: The glucose management protocol resulted in significantly improved glycemic control and was not associated with increased rate of death or hypoglycemia.